Role of A.I.C.T.E. to Ensure Quality in the Changing Scenario - Raju, G. J. V. J. (Journal of Engineering Education Transformations, 2000)
The Technical Education system in India is modelled on straight jacket pattern, which is too rigid allowing little choice for the students in opting for minor areas of study. With globalisation and liberalized economy, new trends are emerging in employment market. The trend shows that the graduates from technical institutions with adequate management background and exposure to information Technology are in greater demand. There is need for AICTE to play a leading role in creating awareness on the necessity for evolving a pattern which suites the changing scenario. The council should evolve an effective mechanism to identify the emerging areas in various fields of technical education and identify requisite changes in curriculum along with the required inputs to improve the quality.